2015
DOI: 10.1007/s10295-014-1558-5
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic deracemisation of aliphatic β-hydroxy esters: Improving the enantioselectivity by optimisation of reaction parameters

Abstract: Optically pure aliphatic β-hydroxy esters were prepared from their racemates by deracemisation using the biocatalyst Candida parapsilosis ATCC 7330. High optical purity (up to >99 %) and good yields (up to 71 %) of the product secondary alcohols were obtained. This study highlights the importance of optimization of reaction conditions using ethyl-3-hydroxybutanoate as the model substrate to improve the enantioselectivity (enantiomeric excess from 9 to 98 %). The present study emphasises the broad substrate sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Whole intact cells which are harvested from the culture media are commonly referred to as resting cells and cell free extract is the crude fraction obtained after lysing the resting cells. Candida parapsilosis ATCC 7330 is reportedly an established biocatalyst for various organic biotransformations to produce optically pure secondary alcohols and amines (Mahajabeen and Chadha 2013 ; Venkataraman and Chadha 2015 ). It is also observed that the biocatalytic activity of this yeast is found to vary with the culture age used for the biotransformation (Kaliaperumal 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whole intact cells which are harvested from the culture media are commonly referred to as resting cells and cell free extract is the crude fraction obtained after lysing the resting cells. Candida parapsilosis ATCC 7330 is reportedly an established biocatalyst for various organic biotransformations to produce optically pure secondary alcohols and amines (Mahajabeen and Chadha 2013 ; Venkataraman and Chadha 2015 ). It is also observed that the biocatalytic activity of this yeast is found to vary with the culture age used for the biotransformation (Kaliaperumal 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though cells harvested at 14 h produced the same ketone at less conversion (38%), these cells were used to visualise the site of biotransformation. For several other substrates reported earlier from our lab, the 14 h harvested cells produced the desired optically pure products with maximum ee (up to >99%) 1 2 3 6 7 26 29 30 33 34 35 .…”
Section: Resultsmentioning
confidence: 69%
“…Earlier reports from our lab have shown that C. parapsilosis ATCC 7330 mediated the asymmetric reduction 1 2 3 27 and deracemisation 4 28 29 30 of aromatic/aliphatic prochiral ketones and secondary alcohols respectively. It seemed logical to use a prochiral ketone for the biocatalytic reduction which shows structural similarity to 1a for the study.…”
Section: Resultsmentioning
confidence: 76%
“…Instead of using isolated enzymes, a number of microbial stereoinversion systems as well as hybrid systems containing whole cells/isolated enzymes have also been reported in deracemisation via stereoinversion. [73][74][75][76][77][78][79][80][81] Here, it should, however, be mentioned that due to the presence of various endogenous ADHs and alcohol oxidases (AOxs) in the microbial "black-box" systems, the real deracemisation pathway may differ case by case from the depiction of Scheme 13; consequently, identifying suitable enantiocomplementary systems can be challenging. Scheme 14 depicts a selection of enantiomerically pure alcohols obtained through enzymatic and microbial deracemisation via stereoinversion.…”
Section: Linear Deracemisation Including Stereoinversion Reactionsmentioning
confidence: 99%
“…Selection of enantiomerically pure alcohols obtained via stereoinversion. [73][74][75][76][77][78][79][80][81] Catalysis Linear deracemisation of amines via stereoinversion For stereoinversion of amines nowadays a broad range of enantiocomplementary ω-transaminases (ω-TAs) are available. The major disadvantage of these methods, however, is that no orthogonal systems are available today.…”
Section: Scheme 14mentioning
confidence: 99%